Penggunaan Metode AHP Dan TOPSIS Untuk Pemilihan Dokter Terbaik - Margana, Ferry Kurniawan; Saputra, Edwin Wira; Adiyarta, Krisna (LPPM UNIKA Santo Thomas Medan, 2020)
The hospital is the only one who handles the patients. Professional and qualified doctors can improve the quality of health services in a health institution. The problem is the existence of subjective assessments between doctors assessed with the appraiser, so that doctors who really deserve the predicate as the best doctor is often not chosen as the best doctor And the absence of information systems that can be used to determine the performance of each physician. The purpose of this research is to create a decision support system for the best performance determination doctor at the Berkah Jaya Medika Indramayu Clinic. The methods used in this acceptance decision support system use the method of Analytical Hierarcy Process (AHP) and Technique for others reference by similarity to ideal solution (TOPSIS). The results of this research is a Web application support system that is based on the decision to provide results in the form of each physician